Pengaruh Corporate Governance terhadap Kinerja Keuangan Perusahaan (Studi pada Sub Sektor Perkebunan Periode 2009 – 2012) - Jannah, Roudhatul (Universitas muhammadiyah palembang, 2014)
The obejective of the study was to determine the influence of corporate governance on corporate financial performance. The problem of the study was whether or not there was influence of corporate governance on corporate financial performance at plantation sub sector. The researchdesign was associative. The study was conducted at plantation sub sector. Dependent variabel was corporate financial performance with the indicators ROE and Tobin’s Q while independent variable was corporate governancewith the indicator were the board of director, independent commisioner, debt to equity and institutional ownership. The data was secondary using financial performance in period 2009-2012 quarterly. The technique of collecting thedata was information technology storage. The technique of analyzis the data were descriptive multiple linear regression. Based on F test showed that corporate governane positively influenced on ROE (Operational Performance) and Tobin’s Q (Market Performance) while t test showed that all indicators of corporate governance also positively influenced on ROE and Tobin’s Q in the other hard, debt to equity negatively influenced on tobin’s Q.